Monday

January 26, 2015

January 26, 2015

Posted by **Rachel** on Monday, November 7, 2011 at 7:24pm.

(tanX-secX)^2= 1-sinX/1+sinX

- Trig -
**declan**, Monday, November 7, 2011 at 7:42pm(sec x - tanx)^2 = (1-sinx)/(1+sinx)

use these substitutions

sin²(x) + cos²(x) = 1

cos²(x) = 1 - sin²(x)

(sec(x) - tan(x))²

=(1/cos(x) - sin(x)/cos(x))²

= (1-sin(x))² / cos²(x)

= (1-sin(x))² / (1 - sin²(x))

= (1-sin(x))² / [(1+sin(x))(1-sin(x))]

= (1-sin(x)) / (1+sin(x))

**Answer this Question**

**Related Questions**

Trig Help - Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx...

Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

trig - How do I prove these trig identities? secx-cosx/tanx =sinx And 1+sinx/...

TRIG - There are two questions of my homework I'm having trouble with.. I think ...

Precalculus/Trig - I can't seem to prove these trig identities and would really ...

Math (Trig) a.s.a.p, thanks! - verify the identities: 1.) 2tanx-(1+tanx)^2 = -...

Math - Im really struggling with these proving identities problems can somebody ...

trig - We are doing trig identities in school. I need help with these five: 1.1+...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...